PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MENGGUNAKAN MODEL PROBLEM BASED LEARNING PADA MATERI BARISAN DAN DERET UNTUK KELAS XI SMA/MA - Ravina Faradilla Syahril; Sehatta Saragih; Susda Heleni (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2021)
This research was done due to the problem found by teachers’ difficulty in developing learning instruments based on the 2013 curriculum. In connection with this, efforts are needed to assist teachers in providing learning instruments that are in accordance with the demands of the 2013 curriculum. The learning instrument form of Syllabus, Learning Implementation Plan (RPP), and Student Worksheets (LKPD). This research aimed to develop mathematics learning instruments. Related to learning management on the 2013 curriculum, one of the recommended learning models is Problem Based Learning (PBL) model. On this basis, the researcher conducted the development of learning instruments by using PBL models on the material sequence and series of class XI SMA/MA by using the 4-D development model. This research instrument used was the Syllabus, RPP, and LKPD sheets to assess the validity of the learning instrument. The results of validation data analysis obtained an average value of the syllabus is 3,76 with a very valid category, RPP is 3,78 with a very valid category and LKPD is 3,75 with a very valid category. Therefore, it can be concluded that the Syllabus, RPP, and LKPD developed are suitable to use for trials in the learning process.